An 8‐week randomized controlled trial comparing the effect of a novel oscillating‐rotating toothbrush versus a manual toothbrush on plaque and gingivitis. (3rd April 2020) - Grender, Julie; Ram Goyal, C.; Qaqish, Jimmy; Adam, Ralf
Abstract : Purpose: To compare a novel oscillating‐rotating (O‐R) electric rechargeable toothbrush with micro‐vibrations (Oral‐B iO) to a manual brush for gingivitis and plaque reduction. Methods: Adult subjects with gingivitis and plaque were randomized to use either the O‐R or the manual toothbrush with standard fluoride dentifrice twice daily. Efficacy was assessed at baseline, week 1, and week 8 using the Rustogi Modification of the Navy Plaque Index (RMNPI), Modified Gingival Index (MGI), and Gingival Bleeding Index (GBI). Gingivitis status ('healthy'/'not healthy') was also assessed, per the American Academy of Periodontology/European Federation of Periodontology criteria. Results: One hundred and ten subjects were enrolled and completed the randomized controlled trial. The baseline mean number (SD) of bleeding sites for all subjects was 32.11 (16.703). At week 8, 82% of subjects using the O‐R toothbrush were categorized as 'healthy' (<10% bleeding sites), versus 24% of subjects using the manual brush ( P  < 0.001). Subjects using the O‐R toothbrush showed statistically significantly greater reductions ( P  < 0.001) in the number of bleeding sites, GBI scores and MGI scores versus those using a manual toothbrush as early as 1 week and throughout the 8‐week study. The O‐R toothbrush also provided statistically significantly greater reductions ( P  < 0.001) in all plaque measures, including sub‐regions, versus the manual toothbrush after a single brushing and at weeks 1 and 8. Conclusions: The novel O‐R electric toothbrush with micro‐vibrations provided statistically significantly greater plaque and gingivitis reductions versus a manual toothbrush, with performance benefits demonstrated after a single brushing and continuing throughout the 8‐week study.